The Role of the elements of the religious views of the tradition maturidia of Central Asian Islamic culture in the society. - Shalkarov., D. B. (Journal of Oriental Studies, 2016)
The basis and directions of the religious views in the medieval Mawarannahr are tightly connected with the Islamic culture. Great scientists as Abu Mansur al-Maturidi, Abu al-Muin al-Nasafi, Abu al-Futuh, Abd al-Gafir al-Kashgari, Imran ibn Israil al-Tarazi, Nasr al-Adib al-Tarazi, Abu Said Mikail ibn Hanifa al- Budahkasi etc….